2018
DOI: 10.1097/ccm.0000000000003083
|View full text |Cite
|
Sign up to set email alerts
|

Short-Latency Positive Peak Following N20 Somatosensory Evoked Potential Is Superior to N20 in Predicting Neurologic Outcome After Out-of-Hospital Cardiac Arrest

Abstract: The absence of P25/30 is related to poor outcome with a higher sensitivity, negative predictive value than the absence of N20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…However, the sensitivity for predicting a poor outcome was different between the two waves. This result is in line with the finding of a study by Kim et al [18]. Although there was an insufficient number of type III SSEPs, all patients who experienced a good outcome showed the presence of both N20 and P25.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the sensitivity for predicting a poor outcome was different between the two waves. This result is in line with the finding of a study by Kim et al [18]. Although there was an insufficient number of type III SSEPs, all patients who experienced a good outcome showed the presence of both N20 and P25.…”
Section: Discussionsupporting
confidence: 92%
“…Cortical N20 and P25 peaks were preserved in all patients with a CPC score of 1–2, whereas a stepwise decrease in the N20 and P25 cortical peaks was detectable in 63% and 59% of patients with a poor outcome, respectively. In a study by Kim et al, a significant decrease in detectable N20 and P25 peaks was observed in 30.9% and 11.1% of patients with a poor outcome, respectively [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of somatosensory evoked potentials (SSEPs) was investigated in 14 observational studies. 199 , 205 , 208 , 209 , 210 , 211 , 214 , 224 , 225 , 226 , 227 , 228 , 229 , 230 In 4 studies, 205 , 224 , 228 , 229 bilaterally absent N20 SSEP wave within 24 hours after ROSC predicted poor neurological outcome from hospital discharge to 6 months. Specificity was 100% and sensitivity ranged from 33.3% to 57.7% (very low-certainty evidence).…”
Section: Postresuscitation Carementioning
confidence: 95%
“…In 12 studies, 205 , 208 , 209 , 210 , 211 , 214 , 225 , 226 , 227 , 228 , 229 , 230 bilaterally absent N20 SSEP wave at 24 to 96 hours after ROSC predicted poor neurological outcome from hospital discharge to 6 months. Specificity ranged from 50% to 100% and sensitivity ranged from 18.2% to 69.1% (very low-certainty evidence).…”
Section: Postresuscitation Carementioning
confidence: 96%